Analisis Faktor Kepuasan Mahasiswa Perguruan Tinggi Swasta di Wilayah Daerah Dilihat dari Kualitas Pelayanan (Studi Multisitus di PTS Kabupaten Tulungagung) - Suprihatin, Vitriani; Suryaningsih, Tutut (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the factors influencing student satisfaction at private universities in the Tulungagung Regency area, viewed from the perspective of service quality. The research was conducted as a multisite study involving three institutions: Bhinneka PGRI University, Hutama Abdi Husada Health College, and Tulungagung University. The background of this research stems from various student complaints regarding staff responsiveness, damaged facilities, and suboptimal academic services. The study employed a qualitative approach using a multisite case study method. The analyzed service quality factors include tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that students still face several issues related to campus services, particularly in facility provision and staff attitudes. Nevertheless, some students expressed satisfaction with certain aspects such as scholarship programs, self-development activities, and faculty support. The study concludes that improving both service quality and facility availability is essential to enhance student satisfaction in private higher education institutions.